Strategi Public Relations Melalui Whatsapp Guna Mempromosikan Pondok Pesantren Asy-Syafi iyah Sukorejo Bangsalsari - Ihyak, Muhammad (Program Studi Ilmu Komunikasi, 2023)
Balancing technological developments and seeing the increasingly diverse competitiveness of Islamic boarding schools because the number of Islamic boarding schools continues to increase every year, for this reason, the Asy-Syafi'iyah Islamic Boarding School also has a strategy in promoting its Islamic boarding schools. The research focus in this thesis is: (1). What is the public relations strategy via WhatsApp to promote the Sukorejo Bangsalsari Asy-Syafi'iyah Islamic Boarding School? (2). Analysis of the advantages and disadvantages of the Public Relations Strategy via Whatsapp to promote the Asy-Syafi'iyah Sukorejo Bangsalsari Islamic Boarding School?. The approach used in this research is a qualitative approach with a descriptive research type and data was collected using observation methods carried out in the field, interviews also carried out in the field, and documentation made in the field. Utilization of Islamic boarding school Public Relations which can help, build and maintain communication between the Islamic boarding school and its public.The results of this research show the Islamic boarding school's public relations strategy in involving public relations and Islamic boarding school alumni to promote Islamic boarding schools using WhatsApp social media. In promoting Islamic boarding schools, public relations and Islamic boarding school alumni form Jami'ah or Islamic boarding school management groups. . Utilizing Whatsapp social media is very effective in promoting Islamic boarding schools. And it can also build good communication between alumni and Islamic boarding school administrators. Alumni maintain good relations with the Islamic boarding school, and also participate in boarding school activities. Then, alumni promote the boarding school by joining the WhatsApp group of the boarding school and the Asy-syai'iyah administrators on each alumni's social media, and holding special alumni events at the boarding school and outside the boarding school. By using WhatsApp social media for alumni and Islamic boarding school administrators, it is easier to promote Islamic boarding schools to the public.